Characteristic of local antichlamydial immunity in infertile women - A. I. Novikov; T. V. Klinyshkova (Бюллетень сибирской медицины)
Objective: to determine the presence of C. trachomatis in upper genital tract and humoral immunity an laparoscopic examination in 202 patients with different infertility factors. Chlamydial persistence in endometrial and tubal tissues was correlated with circulating IgA to C.trachomatis in peritoneal fluid in tubal factor infertility (TFI) (73.5%). IgA may be recommented additional diagnostic factor of chlamydial infection of upper genital tract in TFI.